2019
DOI: 10.1093/eurheartj/ehz203
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of metformin on left ventricular hypertrophy in patients with coronary artery disease without diabetes: the MET-REMODEL trial

Abstract: AimWe tested the hypothesis that metformin may regress left ventricular hypertrophy (LVH) in patients who have coronary artery disease (CAD), with insulin resistance (IR) and/or pre-diabetes.Methods and resultsWe randomly assigned 68 patients (mean age 65 ± 8 years) without diabetes who have CAD with IR and/or pre-diabetes to receive either metformin XL (2000 mg daily dose) or placebo for 12 months. Primary endpoint was change in left ventricular mass indexed to height1.7 (LVMI), assessed by magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 48 publications
(47 reference statements)
3
91
0
1
Order By: Relevance
“…Recently, a randomized controlled trial in patients with coronary artery disease without diabetes demonstrated that metformin significantly reduces left ventricular hypertrophy (LVH), one of the most powerful prognostic factors in coronary artery disease. This study found that metformin largely reduced left ventricular mass indexed to height, left ventricular mass, body weight, and oxidative stress (101). Several studies have reported the benefits of metformin in CVDs and heart failure in patients with or without diabetes, and it will be interesting to explore more possible applications of metformin in the future.…”
Section: Metformin and Cardiovascular Diseasesmentioning
confidence: 58%
“…Recently, a randomized controlled trial in patients with coronary artery disease without diabetes demonstrated that metformin significantly reduces left ventricular hypertrophy (LVH), one of the most powerful prognostic factors in coronary artery disease. This study found that metformin largely reduced left ventricular mass indexed to height, left ventricular mass, body weight, and oxidative stress (101). Several studies have reported the benefits of metformin in CVDs and heart failure in patients with or without diabetes, and it will be interesting to explore more possible applications of metformin in the future.…”
Section: Metformin and Cardiovascular Diseasesmentioning
confidence: 58%
“…Its widespread use has largely been supported by the United Kingdom Prospective Diabetes Study that reported lower cardiovascular mortality and morbidity in patients treated with metformin in comparison with alternative glucose-lowering drugs, despite similar glycemic control [6]. The MET-REMODEL trial proved that metformin treatment can significantly reduce left ventricular hypertrophy and oxidative stress in patients with coronary artery disease without diabetes [7]. Moreover, metformin has been demonstrated to inhibit the Warburg effect thereby exerting an anti-tumor effect [8].…”
Section: Introductionmentioning
confidence: 99%
“…4 These cardioprotective effects appear independent of glycaemic control, suggestive of pleiotropic effects of metformin. 4,5 In patients with T2DM, observational studies suggest that metformin use is associated with a lower risk of new-onset HF. 6 In T2DM patients with pre-existing HF, metformin treatment predicts reduced mortality and hospitalisation.…”
Section: Introductionmentioning
confidence: 99%